Tech-Savvy But Susceptible: The Causes of Computer Crime and its Implications on Young Adults (Gen Z) in Birnin-Kebbi Municipality - Muhammad Sani, Kamal; Abubakar Zagga, Sadiq; Jibril, Hauwa; Bashar Yabo, Abubakar; Umar, Kasimu (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Despite being highly tech-savvy, young adults (Gen Z) are considered among the suitable targets and thus susceptible to experience cyber victimization. This paper is aimed at examining the causes and implications of computer crime on young adults (Gen Z) with special reference to the Birnin-Kebbi municipality. To achieve these goals, the paper adopted the quantitative approach to gather data from 240 (160 males and 80 females) of Birnin-Kebbi’s Gen Z. The survey findings demonstrate that half (67%) of the surveyed Gen Z were involved in computer crime, and 75% were victims of cyberpornography, cyberstalking, phishing attacks, cyberbullying, Ponzi scheme scams, and online dating scams. A significant number of the victims experience depression, anxiety, loneliness, and a decrease in academic performance. The findings also found that factors such as oversharing of personal details, a lack of cybersecurity knowledge, parents’/guardians’ negligence, peer pressure and influence, and the use of unprotected public Wi-Fi contribute to unprecedented involvement in computer crime and cyber victimization. In conclusion, the study recommends that organizing training and workshops on cybersecurity for young adults, reporting incidents of cyber victimization to law enforcement, constant monitoring and supervision of children's online activities, developing and implementing cybersecurity programs in schools, and collaboration between policymakers, law enforcement, religious bodies, traditional rulers, non-profit organizations, and other stakeholders to carry out and raise awareness on the risk of cyber victimization may all assist in combating and reducing the impact of computer crime.